Systematics and ecology of Naiadacarus nepenthicola, a new species of acaridae (Acari: Astigmata) inhabiting the pitchers of Nepenthes bicalcarata hook. f. in Brunei Darussalam - Norman J Fashing; Tock, Hing Chua (Taylor & Francis Group, 2009)
A new species, Naiadacarus nepenthicola, is described from adults and deutonymphs collected in Belait District, Brunei Darussalam, from the fluid-filled pitchers of Nepenthes bicalcarata Hook. f.. This constitutes the first record of a member of the family Acaridae inhabiting Nepenthes pitchers. It is quite probably that N. nepenthicola feeds on decomposing leaves that fall into the pitchers as well as on decomposing insects trapped by pitchers. Dispersal is accomplished through phoresy on Campanotus schmitzi Staercke, an ant that nests exclusively in the hollow tendrils of N. bicalcarata pitchers.